2005
DOI: 10.3354/cr029199
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pacific Decadal Oscillation on relationships between temperature and the Arctic Oscillation in the USA in winter

Abstract: Associated synoptic patterns of the Pacific Decadal Oscillation (PDO) significantly impact relationships between surface air temperature (SAT) and the Arctic Oscillation (AO) across the United States in winter. Using historical data (1900 to 2002) and composite analyses, this study demonstrates that without the influence of the PDO, winter SATs are most significantly altered during various phases of the AO throughout the Ohio Valley region and in the South. More specifically, extreme phases of the PDO signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Rogers and van Loon, 1979;Ramage, 1983Ramage, , 1986Esbensen, 1984;Barnston et al, 1991;Hurrell, 1995Hurrell, , 1996Ropelewski and Halpert, 1996;Jones et al, 1997;Rogers, 1997;Maheras et al, 1999;Stephenson et al, 2000;Wanner et al, 2001;Trigo et al, 2002;Kryjov, 2002;Kutiel and Benaroch, 2002;Fernandez et al, 2003;Xoplaki et al, 2004;Luterbacher et al, 2004;Budikova, 2005;Gallego et al, 2005;Erlat, 2005, 2006;Kim et al, 2006).…”
Section: Introductionunclassified
“…Rogers and van Loon, 1979;Ramage, 1983Ramage, , 1986Esbensen, 1984;Barnston et al, 1991;Hurrell, 1995Hurrell, , 1996Ropelewski and Halpert, 1996;Jones et al, 1997;Rogers, 1997;Maheras et al, 1999;Stephenson et al, 2000;Wanner et al, 2001;Trigo et al, 2002;Kryjov, 2002;Kutiel and Benaroch, 2002;Fernandez et al, 2003;Xoplaki et al, 2004;Luterbacher et al, 2004;Budikova, 2005;Gallego et al, 2005;Erlat, 2005, 2006;Kim et al, 2006).…”
Section: Introductionunclassified
“…Climate divisions have a wide variety of applications beyond simply identifying regions with similar climate types and variability. In the CONUS, studies have shown the influence of climatic teleconnection indices in each division (Wolter et al 1999;Budikova 2005), which is highly valuable for seasonal climatic forecasting. The CONUS climate divisions are currently used as the zones for the seasonal climatic predictions made by the Climate Prediction Center (CPC).…”
Section: July 2012 B I E N I E K E T a Lmentioning
confidence: 99%
“…For example, there is evidence for significant teleconnections between the Pacific Decadal Oscillation (PDO), the Atlantic Multidecadal Oscillation (AMO), the Southern Oscillation, Pacific/North American Oscillation (PNA), and the North Atlantic Oscillation (NAO) and precipitation in the northeast United States [e.g., Richman et al, 1991;McCabe et al, 2004;Notaro et al, 2006a]. The surface air temperatures in this region have also been reported to be closely correlated with PNA, the North Atlantic Oscillation (NAO), the Arctic Oscillation (AO), the Quasi-Biennial Oscillation (QBO), and the East PacificNorth Pacific (EP-NP) pattern [e.g., Leathers et al, 1991;Bradbury et al, 2002;Thompson et al, 2002;Budikova, 2005;Notaro et al, 2006a]. In addition, the El Niño-Southern Oscillation has been reported to affect drought and snowfall over the northeast United States [Ropelewski and Halpert, 1986;Griffiths and Bradley, 2007;Kunkel et al, 2009].…”
Section: Introductionmentioning
confidence: 99%